Plasma of arc discharge between melting Cu- and Ni-electrodes - Veklich, A.N.; Kleshich, M.M.; Fesenko, S.O.; Boretskij, V.F.; Kryachko, L.A. (Вопросы атомной науки и техники, 2018)
The intensity of erosion processes of asymmetric single-component Cu and Ni electrodes of the free burning
electric arc at current of 30 A is studied by measurements of a content metals vapour in plasma column. Optical
emission spectroscopy was used to determine the radial distributions of plasma temperature and electron density in the
middle section of a discharge gap. These experimentally obtained data were used in the calculation of equilibrium
plasma composition. So, the evaporation intensity of each electrode material can be estimated in such indirect way. Досліджували інтенсивність ерозійних процесів вільноіснуючої електричної дуги струмом 30 А між
асиметричними однокомпонентними Cu- та Ni-електродами. У середньому поперечному перерізі розрядного
проміжку за допомогою оптичної емісійної спектроскопії вимірювали радіальні розподіли температури та
електронної концентрації, які використовували для розрахунку рівноважного складу плазми. Отже, у такий
непрямий спосіб може бути оцінена інтенсивність випаровування електродного матеріалу. Исследовали интенсивность эрозионных процессов свободногорящей электрической дуги силой тока
30 А между асимметричными однокомпонентными Cu- и Ni-электродами. В среднем сечении разрядного
промежутка с помощью оптической эмиссионной спектроскопии измеряли радиальные распределения
температуры и электронной концентрации, которые были использованы для расчета равновесного состава
плазмы. Таким косвенным образом может быть оценена интенсивность испарения электродного материала.